Game Factors and Game-Based Learning Design Model. (4th August 2015) - Shi, Yen-Ru; Shih, Ju-Ling
Abstract : How to design useful digital game-based learning is a topic worthy of discussion. Past research focused on specific game genres design, but it is difficult to use when the target game genre differs from the default genres used in the research. This study presents macrodesign concepts that elucidates 11 crucial game-design factors, including game goals, game mechanism, game fantasy, game value, interaction, freedom, narrative, sensation, challenges, sociality, and mystery. We clearly define each factor and analyze the relationships among the 11 factors to construct a game-based learning design model. Two application examples are analyzed to verify the usability of the model and the performance of these factors. It can assist educational game designers in developing interesting games.